Endoscopic sinus surgery : anatomy, three-dimensional reconstruction, and surgical technique - Wormald, P. J. (Thieme, 2018)
As in the acclaimed prior editions, Endoscopic Sinus Surgery, Fourth Edition focuses strictly on anatomy, 3D reconstruction, and step-by-step surgical techniques. Written by Peter-John Wormald, the richly illustrated text details anatomy and operative treatment of sinonasal conditions such as nasal polyposis, chronic rhinosinusitis (CRS), Samter's triad, eosinophilic mucus CRS, exophthalmos, acute orbital hemorrhage, orbital subperiosteal abscess, and a wide array of tumors. The fourth edition reflects simplified anatomical nomenclature published in 2016 by Wormald et al, including reclassification of cells in the frontal recess and the extent of surgery of frontal sinus surgery (EFSS). This enables clearer understanding of impacted anatomy, most notably the frontal sinus drainage pathways. New and revised evidence-based procedures include the mega-antrostomy and pre-lacrimal approach to the maxillary sinus and use of anterior based pedicled flaps for frontal drillout. Refinements in other surgical techniques include endoscopic medial maxillectomy and resection of sinonasal neoplasms.